2014
DOI: 10.1093/rheumatology/keu415
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor inhibitor monotherapy vs combination with MTX in the treatment of PsA: a systematic review of the literature

Abstract: Available evidence on the efficacy and safety of TNF inhibitor monotherapy vs add-on MTX therapy shows little or no improvement with combination therapy, although the use of concomitant MTX appears to prolong TNF inhibitor drug survival of mAb TNF inhibitors. Registries and observational studies have the potential to fill some of the knowledge gaps in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 43 publications
1
47
1
3
Order By: Relevance
“…A randomized trial found that MTX monotherapy did not improve joint counts or other measures of articular disease activity in patients with PsA compared with placebo 5 , suggesting that MTX alone may have minimal clinical effects in this patient population. However, the influence of MTX in combination with TNF inhibitors has not been well studied in PsA 4 . A study based on observational data from Norway did not detect a difference in clinical responses with the concomitant use of MTX and TNF inhibitors, but the authors stressed that they did not have the data to address the issue of peripheral versus axial disease, a major potential confounding factor 8 .…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial found that MTX monotherapy did not improve joint counts or other measures of articular disease activity in patients with PsA compared with placebo 5 , suggesting that MTX alone may have minimal clinical effects in this patient population. However, the influence of MTX in combination with TNF inhibitors has not been well studied in PsA 4 . A study based on observational data from Norway did not detect a difference in clinical responses with the concomitant use of MTX and TNF inhibitors, but the authors stressed that they did not have the data to address the issue of peripheral versus axial disease, a major potential confounding factor 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of TNF results in the downregulation of abnormal and progressive inflammatory processes, resulting in target organ damage. 4,5,10,11,19,27 It has been experimentally proven that TNF inhibitors prohibit organ tissue damage by suppressing the formation of TNF-α, proinflammatory cytokines, and nitric oxide. 5,26,27 A decrease in edema, acinar cell edema, and necrotic cells was observed in Group 3 (p < 0.05) ( Table 2) after the administration of ADA.…”
Section: A B Cmentioning
confidence: 99%
“…3,4 Methotrexate is used to treat many different types of cancer (colorectal, breast, and pancreatic cancers) and inflammatory diseases (rheumatoid arthritis − RA, psoriatic arthritis, systemic lupus erythematosus, and dermatomyositis). [1][2][3][4][5] Nevertheless, its use is associated with side effects such as fibrosis affecting the liver, lung, and other organs. 1,2,5 Acute intense MTX side effects are dose-dependent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations